Towards understanding suicide dynamics in Ghana; Modelling and optimal control application - Shaibu Osman; Chidozie Williams Chukwu; Hailay Weldergiorgis Berhe; Teklebirhan Abraha Gebrehiwot; Oluwole Daniel Makinde; Otoo Dominic; Lema Logamou Seknewna; Abadi Abay; Hawa Osman (Partial Differential Equations in Applied Mathematics)
Suicide is considered a major public health concern, with an estimated 800,000 deaths each year globally. Understanding the dynamics of suicide and identifying effective prevention strategies is paramount. The most common factors responsible for suicidal thoughts are financial challenges, relationship issues, hopelessness, low self-esteem, depression, peer pressure, academic challenges, and parental problems. In this study, we considered suicide as an infection since it is contagious and can be transmitted from one person to the other directly or indirectly. A compartmental modelling approach was employed to help explain the dynamics of this phenomenon with possible strategies to combat this global health challenge. Suicide-free, suicide-endemic equilibrium points and their stability were determined. We extended the suicide model to optimal control using the following variables; education (sensitisation), counselling couples before marriage, and social intervention programmes. It was established that, the best optimal strategy for suicide control is sensitisation and counselling of susceptible population. Numerical simulation was conducted and it confirm the theoretical results. Suicide model has a considerable potential applications to the fight against suicide in Ghana. Policymakers should sensitise the general public on suicide awareness and how to manage financial and marriage related suicides in the country. Religious leaders and organisations should stress the need for counselling before marriage.